Financial efficiency and the ownership of Czech firms - Jan Hanousek; Evézen Koécenda; Michal Maésika (Osteuropa-Institut Regensburg, 2011)
In this paper we analyze the evolution of firm financial efficiency in the Czech Republic. Using a large panel of more than 400,000 Czech firm/years we study whether firms fully utilize their resources, how firm financial efficiency evolves over time, and how firm financial efficiency is determined by ownership structure. We employ a panel ver-sion of a stochastic production frontier model for the period 1996-2007 with time-invariant efficiency. We differentiate among various degrees of ownership concentra-tion and their domestic or foreign origin. In a two-stage set-up we estimate the degree of firm inefficiency and then we estimate the effect of ownership structure on the distance from the efficiency frontier. Our results support the hypothesis that concentration and foreign ownership are positively related to financial efficiency.
Keywords: C33; D24; G32; L60; L80; M21; 330; financial efficiency; ownership structure; firms; panel data; stochastic fron-tier; Finanzierung; Unternehmensentwicklung; Technische Effizienz; Eigentümerstruktur; Schätzung; Tschechische Republik